Social Studies Working Students' Experiences of Online Learning - PEDROSO, JOHN ERWIN; Crudo, Mark Louie; Magno, Lester; Mellizo, Heart (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2022)
Working students felt the impact of the uncertainties brought by the pandemic and faced issues influenced by various factors such as time constraints, home-schooling, and limited workspaces at home. This descriptive phenomenological qualitative study focused on describing the experiences of social studies working students during the COVID-19 pandemic. This study was conducted among six (6) social studies working students determined through purposive sampling. The data were gathered using a duly-validated researcher-made questionnaire administered through online platforms such as messenger and e-mail. The accumulated data was then analyzed using conventional qualitative content analysis. Social studies working on students’ experiences of online learning during the COVID-19 pandemic emerged to have three (3) major themes which are motivational experiences, roadblock experiences, and coping experiences, and six (6) major categories. The motivational experiences considered by social studies working students to pursue working while studying encompasses intrapersonal motivation and interpersonal motivation. Furthermore, during the course of their working-while-studying experience, they faced roadblock experiences such as challenges encountered and thoughts of discontinuing. In light of this, social studies working students had coping experiences namely coping with responsibilities and coping with feeling overwhelmed which helped them cope up with the demands of their duties. Delving into the experiences of social studies working students during the COVID-19 pandemic is critical in order to understand what they were going through. It is vital that these individuals' lived experiences be considered, knowing that they constitute an essential part of society.